About external sources of the magnetic field variations on Academic Vernadsky observatory during a magnetic storm on April, 6-7th 2000 - Maksimenko, O. I.; Bakhmutov, V. G.; Melnyk, G. V.; Shenderovskaya, O. Ya. (Ukrainian Antarctic Journal, 2008)
Changes of modelling magnetic fields of the basic current sources (the ring current RC, including symmetric SRC and asymmetric partial RC PRC, a cross-section current of a magnetospheric tail, the Birkeland’s longitudinal currents), composing a magnetospheric total field disturbances, along the magnetic field lines on a meridian of an Academic Vernadsky observatory for the main phase of a magnetic storm on April, 6-7th 2000 are considered. The calculations of the geometry of the magnetic field lines and a magnetic field of the magnetospheric disturbances by Tsyganenko’s model T01 for the investigation of the distributions of the magnetic fields in the internal magnetosphere have been used.